INNOVATIVE STRATEGIES IN CONTEMPORARY DA'WAH: INITIATING A TECHNOLOGY-BASED APPROACH: INNOVATIVE STRATEGIES IN CONTEMPORARY DA'WAH: INITIATING A TECHNOLOGY-BASED APPROACH - Hanif , Muhammad; Agusman (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
Facing the changing dynamics of contemporary society, da'wah as a means of spreading religious values needs to adopt innovative strategies. In an effort to understand and face the changing times, this paper aims to analyze the potential use of technology in supporting the effectiveness of da'wah, as well as initiating a more adaptive approach to the demands of modern audiences. This research method is based on literature analysis by collecting data from various relevant sources. The results of this study identify changes in people's behavior in interacting with technology and their impact on the delivery of religious messages. In this context, innovative technology-based strategies are proposed as solutions to bridge the gap between the tradition of da'wah and the needs of the times. The research findings underscore the potential of technology in creating a more personalized interaction between the conveyor and receiver of da'wah messages. The technology-based approach allows the adaptation of religious messages into formats that are more interesting and relevant to the characteristics of modern audiences. This opens up opportunities to reach a wider and deeper audience. Keywords : Da'wah; Technology; Innovative.